Association of vitamin D(3) with alveolar bone regeneration in dogs - Hong, Hsiang-Hsi (J Cell Mol Med, 2015)
Designed sockets prepared on the mandibles of nine Beagle dogs were divided into three groups: Calcitriol +Alloplast, Alloplast and Empty. Five of the nine dogs received Vit.D(3) and calcium supplement (Vit.D/Ca group), while the other four dogs without supplements were assigned to Non-Vit.D/Ca group. After 4 weeks, the extent of vertical ridge resorption (VRR), bone density (density), new bone formation (NBF) and implant stability quotient (ISQ) were measured. Following systemic Vit.D/Ca administration, the Empty subgroup showed significant differences from the Calcitriol + Alloplast subgroup on variants NBF/Density/VRR and the Alloplast subgroup on items NBF/Density/ISQ/VRR. Alternatively, the Calcitriol + Alloplast subgroup revealed higher values of NBF/Density/ISQ (P < 0.001) and a lower VRR value (P = 0.001) than the Alloplast subgroup. Although there were no significant differences in NBF (P = 0.349), density (P = 0.796), ISQ (P = 0.577) and VRR (0.979) comparisons on alloplast treatment between the Vit.D/Ca and Non-Vit.D/Ca groups, local application with Calcitriol + Alloplast demonstrated better NBF/Density/ISQ (P = 0.02 to <0.001) effects than which of Alloplast subgroups. Consequently, the results showed that both systemic and local vitamin D(3) treatment might accelerate bone regeneration in dogs. Within the using dose, systemic vitamin D(3) treatment displayed a superior stimulating effect than local vitamin D(3) application did.